REPRESENTATION OF 'OTHER' IN MALAYSIA FILM: KADAZANDUSUN IDENTITY IN SABAH INDIGENOUS TELEMOVI - Sydney Thomas, Sibangan; Teo, Miaw Lee; Candida Jau, Emang (NVEO - Natural Volatiles & Essential Oils, 2021)
Malaysia, as a multicultural society, is made up of various ethnic groups with diverse backgrounds. From a national perspective, the need for racial integration into a single national identity is critical in order to structure unity among Malaysians. Under the strict supervision of the local government, a film in Malaysia plays an important role in incorporating the diverse society by portraying the accepted Malaysian national identity. However, the concept of national identity is based on an 'imagined' assumption because Malaysian national cinema is dominated by and exclusively represents the Malay majority. As a result, there is a lack of representation in film for 'other' ethnic groups, particularly Sabah's indigenous people. Using Benedict Anderson's theoretical framework of "imagined communities," this paper attempts to situate Sabah indigenous film within the context of Malaysian national cinema and argue the distinction of self-identification possessed by the Sabah indigenous. This is accomplished by examining two Alfred Ujin-produced Kadazandusun telemovies. The paper concludes that indigenous ethnic groups in Sabah identified themselves independently of national identity. Indigenous filmmakers used film to express their identity by depicting indigenous language, culture, and values.